The Effects of Gadget Use on Students' Communication Ethics and Styles: A Quantitative Comparative Study - Aurillia, Dessya Angelica; Wulandari, Murfiah Dewi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study examines the impact of gadget-use intensity on elementary students' communication ethics and communication styles. It further compares these two dimensions between high- and low-intensity user groups to understand how digital exposure shapes students' social interaction patterns. Methods: A quantitative comparative design was employed involving 200 Grade IV and V students in Surakarta selected through stratified random sampling. Three variables were measured using a structured questionnaire: Intensity of Gadget Use (X), Communication Ethics (Y₁), and Communication Style (Y₂). Instrument development was informed by social learning theory and media effects theory. Validated items (r = .446–.775) demonstrated sufficient reliability (α = .612–.764). Data analysis included MANOVA and follow-up independent-samples t-tests, with results reported using international statistical standards. Results: MANOVA indicated a significant multivariate difference between high- and low-intensity groups, F(2,197) = 4.316, p = .015, η² = .042, representing a small effect size. Subsequent t-tests revealed no significant difference in communication ethics (p = .187), but a significant difference emerged in communication styles (p = .012), indicating that higher gadget-use intensity is associated with more digitally oriented communication behaviors. Applications/Originality Value: This study addresses an unexamined gap by simultaneously analyzing communication ethics and communication styles. Findings suggest that gadgets influence students' communicative patterns more strongly than their ethical orientation, offering implications for digital literacy programs in elementary education.